Recognition of the Emotional Content of Music Depending on the Characteristics of the Musical Material and Experience of Students - Knyazeva T.S., (Психологическая наука и образование (2007. Online), 2015)
We studied the effect of the factors affecting the recognition of the emotional content of the music. We tested hypotheses about the influence of the valence of the music, ethnic style and the listening experience on the success of music recognition. The empirical study involved 26 Russian musicians (average age of 25,7 years). For the study of musical perception we used bipolar semantic differential. We revealed that the valence of music material affects the recognition of the emotional content of music, and the ethno style does not. It was found that senior students recognize the emotional context of the music more effectively. The results show the universal nature of emotional and musical ear, equally successfully recognizing music of different ethnic style, as well as support the notion of higher significance of negative valence of emotional content in the process of musical perception. A study of factors influencing the emotional understanding of music is important for the development of models of emotion recognition, theoretical constructs of emotional intelligence, and for the theory and practice of music education.